2019
DOI: 10.1002/ejoc.201900664
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious and Environmentally‐Benign Approach to 2‐Aryl/Heteroaryl Selenopyridines via Ruthenium Catalyzed [2+2+2] Cycloadditions

Abstract: A highly efficient protocol for the synthesis of 2‐aryl/ hetero aryl selenopyridines has been developed via a ruthenium(II)‐catalyzed cycloaddition reaction of 1,6‐diynes with aryl/heteroaryl selenocyanates with good to excellent yields. It was found that various diynes and selenocyanates expediently underwent the reaction under open‐flask conditions. This atom‐economical catalytic strategy offers a mild and practical approach to access a variety of such cycloadducts with excellent regioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Over the past decade, aryl selenocyanates (ArSeCN) have attracted considerable attention since they displayed biological activity [2] and found wide applications in organic synthesis. For example, aryl selenocyanates have appeared as an important organoselenium reagent to construct various organic selenium compounds including monoselenides, [3a–e] diselenides, [3f,g] trifluoromethyl (difluoromethyl) selenides, [3h,i] selenoesters [3j] and selenium‐containing ligands [3k] . In some cases, aryl selenocyanates could serve as a useful bifunctional reagent for the direct cyanoselenenylation of unsaturated C−C bonds [4]…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, aryl selenocyanates (ArSeCN) have attracted considerable attention since they displayed biological activity [2] and found wide applications in organic synthesis. For example, aryl selenocyanates have appeared as an important organoselenium reagent to construct various organic selenium compounds including monoselenides, [3a–e] diselenides, [3f,g] trifluoromethyl (difluoromethyl) selenides, [3h,i] selenoesters [3j] and selenium‐containing ligands [3k] . In some cases, aryl selenocyanates could serve as a useful bifunctional reagent for the direct cyanoselenenylation of unsaturated C−C bonds [4]…”
Section: Methodsmentioning
confidence: 99%
“… The same year, Goswami reported related [2+2+2] cycloadditions of 1,6-diynes with 3-thiocyanatoindoles to form 3-(2-thiopyridyl)­indoles (Scheme ). Later in 2019, Goswami described analogous [2+2+2] cycloadditions of 1,6-diynes with selenocyanates or aryl cyanates to form selenopyridines , and 2-aryloxypyridines, respectively (not shown). In 2018, in [2+2+2] cycloadditions of 1,6-diynes with acetylenic nitriles, Goswami found that neutral Cp*Ru catalysts provide benzonitriles ( vide supra , Scheme ), whereas cationic Cp*Ru catalysts (generated in situ from Cp*RuCl­(cod) and AgOTf) provide 2-alkynylpyridines (Scheme ).…”
Section: Six-membered Ring Formationmentioning
confidence: 97%
“…In a related study, Goswami and co-workers examined the same reaction under 'open-flask' conditions, using 2 mol% [Cp*RuCl(cod)] in ethanol at room temperature and a range of 2-[(hetero)arylseleno]pyridines were prepared in 82-90% yield (Scheme 79). 141 Unsymmetrical 1,6-diynes were also employed for this cycloaddition with selenocya- This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Scheme 78mentioning
confidence: 99%